Commercial Community Spaces Redevelopment: A Case Study of Shanghai Xintiandi Area - Sun, Jiadai (Transactions on Social Science, Education and Humanities Research, 2024)
In the delicate process of revitalizing and preserving Shanghai's iconic Shikumen architecture, a profound question emerges—how conscientiously safeguard the warmth and authenticity inherent in traditional cultural elements while concurrently nurturing the evolution of public commercial spaces nestled within the historic alleyways? This endeavor necessitates a nuanced approach that navigates the intricate balance between preservation and progress, aiming to avoid the perilous pitfalls of homogenization frequently witnessed in contemporary commercial developments. This paper categorizes and examines the issues and challenges faced by historical buildings in the Shikumen area of Shanghai during urban renewal. It explores the successful example of Xintiandi, highlighting valuable methods and insights for urban development in China. Additionally, the author compares Xintiandi in Shanghai with Nanluoguxiang in Beijing, emphasizing key issues such as commercial homogenization and the over-commercialization of distinctive historical urban districts, as seen in the case of Nanluoguxiang. This introduction, sets the stage for a comprehensive exploration of the nuanced challenges faced in the revitalization of Shikumen architecture. The subsequent discourse will delve into strategies and considerations that go beyond the superficial, seeking to establish a blueprint for the coexistence of tradition and commerce in these venerable alleyways.